The Role of Aqidah Akhlak Teachers in Forming Good Character of Students at MTs Al-Ghazali Jatibarang - Ahmad Kurnia; Didik Himmawan (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
This study is entitled the role of aqidah akhlak subject teachers in shaping good character of students in class 8 MTs Al-Ghazali Jatibarang. This study aims to determine the role of aqidah akhlak subjects in shaping students' character to be better. The method used to conduct the study is a qualitative approach method where the sample for the study was 7 students of class 8 MTs Al-Ghazali. Data collection was carried out using questionnaires and direct interviews with students. From the results of this study, it can be concluded that aqidah akhlak lessons play a very important role in shaping the character of students because students' characters are formed by providing good materials and teachers also provide good examples to their students so that students can imitate this. Teachers really have to show their professional attitude when teaching. therefore, as teachers, they must be able to teach with patience, not easily emotional and sincere.